AL QURAN SEBAGAI BUKU METODE PEMBELAJARAN: ANALISIS AYAT-AYAT TARBIYAH: AL QURAN SEBAGAI BUKU METODE PEMBELAJARAN: ANALISIS AYAT-AYAT TARBIYAH - Sahrizal Fahlawi; Rizka Eliza Pertiwi; Heri Fadli (JURNAL MAHASANTRI, 2023)
This article discusses the Al Quran as a book of learning methods.The Al Quran discusses various topics about social life, including education, which discusses learning methods which are a medium for conveying messages from teachers to students.The learning method plays an important role in the learning process and even determines the level of achievement of learning objectives.In the Al-Quran there are several learning methods with various variants that can be used as references for teachers.Verses discussing learning methods can be found in verses discussing educational issues or better known as tarbiyah verses.This article discusses various methods in learning and the role of the method itself. Keywords: Al Quran, Metode Pembelajaran, Ayat-ayat Tarbiyah